How long were older people expected to live with or without sarcopenia? Multistate modeling of a national cohort study - Ye, Bo; Wang, Yujie; Xu, Jixiang; Jiang, Junjia; Yang, Shitong; Chen, Jie; Bao, Zhijun; Gao, Junling (Frontiers in Public Health, 2023)
Objectives: Sarcopenia is a well-known risk factor for mortality, but there is currently insufficient evidence on the estimates of life expectancy (LE) for sarcopenia in China. This study aims to estimate the total life expectancy (TLE) and sarcopenia-specific LE in community-dwelling older adults in China, both with and without sarcopenia. Methods: This study analyzed participants aged 60 and older who enrolled in the China Health and Retirement Longitudinal Study (CHARLS) cohort in 2011 and 2013 and completed at least one follow-up until 2015. Sarcopenia was defined according to the Asian Working Group on Sarcopenia 2019 criteria. We estimated the total and sarcopenia-stratified LE for the overall and subpopulations using continuous-time multistate modelling. Results: A total of 6029 participants (49.2% women) with an average age of 68.4 (SD: 6.56) years were included in the study. The baseline prevalence of sarcopenia and possible sarcopenia was 19.5% and 44.9%. We observed naturally deterioration of sarcopenia stages to worse stages (include death, 24.4%) and reversion to better stages (17.1%) during a median follow-up of 3.92 years (IQR: 2.00~4.00). The average TLE at age 60 was 20.9 [95%CI: 20.2-21.5] years, with 22.1 [95%CI: 19.6-24.6] years for non-sarcopenic, 20.9 [95%CI: 19.5-22.3] years for possible sarcopenic, and 18.7 [95%CI: 16.4-21.1] years for sarcopenic older adults. Men, former and current smokers, and those living in the northwest of China had shorter TLE. Sarcopenic older adults, those with lower education, unmarried status, agriculture hukou, and living in rural area and the northwest of China were expected to live fewer years with non-sarcopenia. Sarcopenic older people, men, those with agriculture hukou, living in rural area and the southwest of China were expected to live more years with sarcopenia. Discussion: These findings enhance our understanding of the relationship between sarcopenia and life expectancy. We suggest that targeted strategies should be considered in high-risk population and underdeveloped regions to prevent sarcopenia and improve non-sarcopenic life years for older adults.